Osteopenia prematuritas dan upaya pencegahannya - Febriyanti Mobilina; Guslihan Dasa Tjipta; Emil Azlin; Pertin Sianturi; Bugis Mardina Lubis; Beby Syofiani Hasibuan (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Osteopenia of prematurity is a common problem encountered in preterm infants or infant with low birth weight. This is characterized by decreased bone mineral content due to inadequat nutritional intake and biochemical factors. This condition can make metabolic disorders in pathological bone fractures even in newborns. Incidence of osteopenia in low birth weight infants in 30%, whereas in infants less than 1000 g of about 55%, and infants less than 1500 g as much as 23%. For preterm infants, the features commonly associated with fracture are delivery at less than 28 weeks of gestation. Metabolic bone disease is often not detected at early stage and became known after appearing obvious abnormalities in the bone or in radiologic examination. Therefore, it is necessary to screening with serum biochemical examination of blood in serum levels of calcium, phosphate and alkaline phosphatase. In addition, it was important to intake of calcium and phosphorus are sufficient for bone mineralization. Key word : osteopenia of prematurity, preterm, calcium, calcium